Collaborative Innovation in Professional Sport Stadium Construction: An Event History Analysis - Sungil Hong; Mar Magnusen; Dennis Coates (Journal of Applied Sports Management, 2019)
This study identifies and empirically tests a variety of potentially important deter-minants influencing new stadium construction adoption from both a team and government perspective, while also accounting for the role of diffusion effects in new stadium construction. The sample consists of 28 Major League Baseball (MLB) franchises in 26 cities in the U.S. Given the longitudinal nature of the stadium con-struction process, event history analysis (EHA) was employed as the primary sta-tistical method. Overall, 48% of the variance was explained by the research model. Diffusion effects (measured as divisional diffusion and regional diffusion) were found to be the most meaningful to construction adoption. The significance of this study rests in its focus on identifying and empirically testing factors influencing the adoption of sport stadium construction from the perspectives of professional sport teams and governing bodies. The empirical results support Rogers (2003) diffusion of innovation theory and provide useful information to both sport managers and governments officials on key factors (e.g., diffusion effects) that may increase the prospect of stadium construction adoption.
Keywords: Diffusion effects; governance; policy; professional sports; stadium financing